Inari Saami geminates - Türk, Helen; Lippus, Pärtel; Pajusalu, Karl; Teras, Pire (2018)
Data extracted from the Inari Saami prosody corpus (http://dx.doi.org/10.15155/1-00-0000-0000-0000-00150L), used in Türk et al (2018). The Acoustic Correlates of Quantity in Inari Saami. Journal of Phonetics. Target words with six different foot structures were used: CVCV, CVCCV, CVC:CV(C), CVVCV(C), CVVCCV(C), CVVC:CVC. In total there were 1463 words included in the analysis of durations, 1043 for fundamental frequency and 597 for intensity measures.